2003
DOI: 10.1021/jo034762z
|View full text |Cite
|
Sign up to set email alerts
|

Michael Addition of Amines and Thiols to Dehydroalanine Amides:  A Remarkable Rate Acceleration in Water

Abstract: In water, the rate of Michael addition of amines and thiols to dehydroalanine amides was greatly accelerated, leading to shorter reaction times and higher yields. The scope of the new conditions was tested with a range of amines, thiols, and dehydroalanine amides. The ease and efficiency of this method provides an attractive route to the synthesis of natural and unnatural amino acid derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…23 Importantly, Naidu et al reported a dramatic increase in both the rate and yields in the Michael addition of amines and thiols to dehydroalanine amides upon using THF:water or methanol:water as the solvent. 24 A similar rate enhancement was observed in the aza-Michael addition of cyclam to phenyl vinyl sulfone and phenyl vinyl sulfoxide when water was added to the reaction mixture. 25 However, in the case of vinyl sulfonamides, it was not known if there is any rate acceleration of the aza-Michael addition in the presence of water in the solvent system.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…23 Importantly, Naidu et al reported a dramatic increase in both the rate and yields in the Michael addition of amines and thiols to dehydroalanine amides upon using THF:water or methanol:water as the solvent. 24 A similar rate enhancement was observed in the aza-Michael addition of cyclam to phenyl vinyl sulfone and phenyl vinyl sulfoxide when water was added to the reaction mixture. 25 However, in the case of vinyl sulfonamides, it was not known if there is any rate acceleration of the aza-Michael addition in the presence of water in the solvent system.…”
supporting
confidence: 53%
“…24 Indeed, this proved to be correct. In the aza-Michael addition of benzyl amine (1 eq) to vinyl sulfonamide 1 (1 eq) we observed significant increase in the rate of reaction, when the reaction was run in a 2:3 mixture of methanol/water for 18 hours.…”
mentioning
confidence: 90%
“…Usually, a tertiary amine is selected as catalyst for the conjugate addition, [27] since primary amines are prone to react with a, b-unsaturated compounds, a reaction that decreases the yield of the thiol Michael addition. [28,29] In our procedure, the a, b-unsaturated ester was added in excess, relative to the total thiol concentration, consisting of the two polymer end groups and the 1-isobutylthiol by-product. The low molecular weight Michael addition by-products were removed entirely by reprecipitations of the polymers, as shown by the absence in the NMR spectra of P-2 and P-3 of signals in the region between 0.9 and 1.0 ppm where resonances of the methyl groups of butylthiourea, isobutylthiol and butylamine appear (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sortase Converts AAEKs to Reactive Olefin IntermediatesWe hypothesized that the ␤-carbon of AAEK1 or AAEK2 may be linked via Michael-type addition by the sortase thiol to an olefin intermediate generated by amine elimination (42,43). If so, addition of exogenous thiol would be expected to "capture" the olefin intermediate, thereby preventing the modification of (Fig.…”
Section: Resultsmentioning
confidence: 99%